2003
DOI: 10.1128/mcb.23.17.6210-6220.2003
|View full text |Cite
|
Sign up to set email alerts
|

BAF60a Mediates Critical Interactions between Nuclear Receptors and the BRG1 Chromatin-Remodeling Complex for Transactivation

Abstract: Nuclear hormone receptors are ligand-dependent transcriptional regulators that modulate chromatin structure. However, the precise molecular mechanisms by which receptors recruit chromatin-remodeling activity are not fully elucidated. We show that in the absence of its ligand-binding domain, the glucocorticoid receptor (GR) is able to interact with both nuclear receptor coactivators and the BRG1 chromatin-remodeling complex in vivo. Individually, the GR makes direct interactions with BRG1-associated factor 60a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 52 publications
5
148
0
2
Order By: Relevance
“…Each has one or more alternative transcripts that add to the complexity of the SWI/SNF complex. BAF60A has been linked to lung cancer risk (Gorlov, 2005), binds to p53 and is necessary for steroid receptor function (Hsiao et al, 2003). Baf60C is expressed specifically in the heart and somites in the early mouse embryo (Lickert et al, 2004).…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…Each has one or more alternative transcripts that add to the complexity of the SWI/SNF complex. BAF60A has been linked to lung cancer risk (Gorlov, 2005), binds to p53 and is necessary for steroid receptor function (Hsiao et al, 2003). Baf60C is expressed specifically in the heart and somites in the early mouse embryo (Lickert et al, 2004).…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…work has shown that GR makes direct contacts not necessarily with BRG1 but with the BRG1-or BRM-associated factors, BAF 57 and BAF60a (Hsiao et al, 2003).…”
Section: Molecular Biology Of the Cell 3312mentioning
confidence: 99%
“…To establish the role of the SWI/SNF complex in the transcriptional regulation of the MMTV-LTR, we carried out transcription reporter assays in the human adrenal carcinoma cell line (SW13). The SW13 cell line expresses all the BAFs and the SWI/SNF complex can be reconstituted by transfecting BRG1 or BRM into this cell line (Muchardt and Yaniv, 2001;Hsiao et al, 2003). This model system has allowed us to assess the contribution of each chromatin remodeling protein to the hormone-dependent regulation of MMTV transcription.…”
mentioning
confidence: 99%
“…The interaction between GR and BRG1 appears to be mediated through BAF250 and/or BAF60a of SWI/SNF. Glucocorticoid receptor binding of BAF60a takes place in a ligand independent manner, but is required for efficient GR-mediated transcriptional initiation and remodeling of the MMTV promoter in vivo (Hsiao et al, 2003). By contrast, the interaction between GR and BAF250 seems to be dependent on the presence of ligand .…”
Section: Role Of Swi/snf In Nr-mediated Transcription Regulationmentioning
confidence: 99%
“…Recruitment of the SWI/SNF complex is not limited to the type I NRs. The remodeling complex has also been found to associate with transcription activation of RAR/ RXR and VDR/RXR indicating involvement of SWI/SNF in a wide range of NR-mediated events (Hsiao et al, 2003;Koszewski et al, 2003).…”
Section: Role Of Swi/snf In Nr-mediated Transcription Regulationmentioning
confidence: 99%